Evaluation of the increased load bearing capacity of steel beams strengthened with pre-stressed FRP laminates (Fracture and Structural Integrity, 2016)
We analyse the problem of a simply supported steel beam subjected to uniformly distributed load, strengthened with a pre-stressed fibre-reinforced polymer (FRP) laminate. We assume that the laminate is first put into tension, then bonded to the beam bottom surface, and finally fixed at both its ends by suitable connections. The beam and laminate are modelled according to classical beam theory. The adhesive is modelled as a cohesive interface with a piecewise linear constitutive law defined over three intervals (elastic response, softening response, debonding). The model is described by a set of differential equations with suitable boundary conditions. An analytical solution to the problem is determined, including explicit expressions for the internal forces and interfacial stresses. As an application, we consider the standard IPE series for the steel beam and the Sika® CarboDur® system for the adhesive and laminate. For each considered cross section, we first carry out a preliminary design of the unstrengthened steel beam. Then, we imagine to apply the FRP strengthening and calculate the loads corresponding to the elastic limit states in the steel beam, adhesive, and laminate. Lastly, we take into account the ultimate limit state corresponding to the plasticisation of the mid-span steel cross section and evaluate the increased load bearing capacity of the strengthened beam. KEYWORDS. Steel beam; FRP strengthening; Adhesive; Beam theory; Cohesive-zone model; Analytical solution; Pre-stressing; Ultimate limit state; Load bearing capacity.
Keywords: Steel beam; FRP strengthening; Adhesive; Beam theory; Cohesive-zone model; Analytical solution; Pre-stressing; Ultimate limit state; Load bearing capacity